Resource utilization status and development trend of bulk solid waste of coal-based ash/slag - Jinwen WU; Xiaowei DENG; Feishuo JIAO; Bo LYU; Chaojun FANG (Meitan kexue jishu, 2024)
In recent years, the rapid development of the coal industry has provided important energy security and raw material support for the national economy. At the same time, coal-fired power plants, industrial, civil boilers and other equipment produce large quantities of coal-based ash/slag (fly ash, coal-fired slag, gasification slag) and other industrial solid waste during the coal combustion and gasification processes, which have a significant impact on the ecological environment.Taking coal-based ash/slag represented by fly ash and gasification slag as an example, China emits about 800 million tons of fly ash and 35 million tons of gasification slag every year. However, limited by the national energy structure, industrial policy and other factors, as well as the resource distribution of coal-based ash/slag and the nature of the origin of the constraints. At present, the efficient resource utilisation of coal-based ash/slag is still to be improved. Among them, the comprehensive utilization rate of fly ash is 70%, and that of gasification slag is only 30%. In the future, China's bulk solid waste still faces the dilemma of large output, inadequate utilization of resources and low added value of comprehensive utilization products. Therefore, to further improve the comprehensive utilization level of bulk solid waste, comprehensively improve the efficiency of resource utilization, actively implement the national ‘carbon peak’ and ‘carbon neutrality’ related policies.Completing the relevant work in the ‘14th Five-Year Plan’ of the coal industry is an important issue for coal development and utilisation at present. Based on this, a lot of exploration has been carried out for the properties of coal-based ash/slag, such as classification, separation, quality and other technical research. Targeted process technologies and equipment have been developed, partially realising bulk solid waste resource utilisation and high value-added utilisation of coal-based ash/slag. In view of the characteristics of coal-based ash/slag with large specific surface area, developed pore structure, high carbon content, rich in aluminium and silicon content, it has been widely used as a raw material in construction and building materials, environmental protection, ecology, chemical industry and other fields.In this paper, the utilization of bulk solid waste resource and the utilization of high value-added in deep processing of coal-based ash/slag are discussed. ① Construction, building materials and other application fields are still important directions to improve the resource utilization of bulk solid waste of coal-based ash/slag. However, due to the problems of coal-based ash/slag resource utilization, such as decarbonization, carbon-ash separation technology, equipment need to be improved, difficulties in dewatering and drying, and possible precipitation of heavy metals, etc., which need to be followed up with in-depth research. ② Extraction of useful components and used in the preparation of functional carbon materials, environmental pollution control and other fields can realize the deep processing of coal-based ash/slag with high value-added utilization. However, it is necessary to effectively treat the acid, alkali or heavy metal waste liquid generated in the production process to reduce the pollution to the environment. In view of the existing problems in the resource utilization of bulk solid waste of coal-based ash/slag, its future development trend was discussed.It is expected to provide reference for the resource utilization of bulk solid waste of coal-based ash/slag as well as the high-end, low-carbon and green development of the coal chemical industry.